Robot-assisted splenectomy in a teenager with chronic autoimmune thrombocytopenia - Silvia Bisoffi; Costanza Tognon; Laura Sainati; Antonio Marzollo; Michele Battistel; Francesco Fascetti Leon; Piergiorgio Gamba (Elsevier, 2020)
The use of the Da Vinci Xi system is gaining popularity among all surgical disciplines. A splenectomy is a treatment option for patients with hematological disorders and splenic lesions. The laparoscopic approach is nowadays the standard of care. Despite the initial controversy, recently it has been demonstrated the superiority of robotic splenectomy performed in ''difficult'' cases. We report, to our knowledge, the first case of robot-assisted splenectomy following embolization of the splenic artery in a 15-year-old patient with chronic immune thrombocytopenia, worsened by a severe cerebral sinus thrombosis, while being treated with eltrombopag and mycophenolate. Due to the need for a rapid rise in platelet counts and failure of several medical treatments, splenectomy was advocated. To raise the platelet count pre-operatively and minimize intraoperative bleeding, the embolization of the spleen artery was performed before the planned splenectomy. The intervention was carried on without any complication and at 1 year follow up the patient is in good clinical condition and has improved his neurological condition. We propose a robotic splenectomy following embolization of the splenic artery as a feasible and safe procedure. The advantages of the Da Vinci Xi system are highlighted especially in complex cases, requiring maximum precision.